The educational practices and pathways of South African students : across power-marginalised spaces - Fataar, Aslam (Sun Press, 2018)
The lived experiences of students' educational practices are analysed and explained in terms of the book's plea for the recognition of the 'multi-dimentionality' of students as educational beings with unexplored cultural wealth and hidden capitals. The book presents an argument that student lives are entangled in complex social-spatial relations and processes that extend across family, neighbourhood and peer associations, which are largely misrecognised in educational policy and practice. The book is relevant to understanding the role of policy, curriculum and pedagogy in addressing the educational performance of working-class youth.